Pemaknaan Karyawan terhadap Corporate Social Responsibility dan Sustainable Development pada Perusahaan Manufaktur dan Jasa - Emma Budi Sulistiarini; Imaduddin Bahtiar Efendi; Uyun Nadzirotul Faidah; Chindy Alvionita Bana Pah (Jurnal Aplikasi Ilmu Teknik Industri (JAPTI), 2026)
This study examines how employees in manufacturing and service firms interpret Corporate Social Responsibility (CSR) and Sustainable Development in their organizational context. The study is motivated by the continuing debate on whether CSR and Sustainable Development are understood as identical, different, or overlapping concepts in business practice. A descriptive qualitative approach was employed. Data were collected through semi-structured interviews with 11 employees working in manufacturing, service, and construction-related service contexts in East Java, Indonesia. The data were analyzed using descriptive thematic analysis, including data reduction, coding, categorization, interpretation, and conclusion drawing. The findings show that employees interpret CSR and Sustainable Development in different ways. Some employees understand CSR mainly as charity or social donation. Others interpret CSR as part of Sustainable Development, especially when company programs are related to environmental preservation, education, health, and community empowerment. The study also finds that internal communication and employee involvement play important roles in shaping employees’ understanding of the relationship between CSR and Sustainable Development. These findings imply that companies need not only to implement CSR programs, but also to communicate them clearly and align them with long-term sustainability objectives so that employees can understand and support them as internal stakeholders.